Pengaruh Program Pelatihan Terhadap Kreativitas Motif Sulaman Karawo di UMKM Serasi - Rahmawati Zakaria; Irina Popoi; Melizubaida Mahmud; Sudirman Sudirman (State University of Gorontalo, 2023)
The present research aimed to determine the effect of the training program on the creativity of Karawo (Traditional Fabric of Gorontalo) embroidery motifs at UMKM (Micro, Small, and Medium Enterprises) Serasi, Dulomo Selatan Village, Kota Utara Subdistrict, Gorontalo City. This research employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to customers at UMKM Serasi, Dulomo Selatan Village, Kota Utara Subdistrict, Gorontalo City, with a total sample of 30 respondents. At the same time, the date analysis technique used simple linear regression. The finding revealed that the training program affected the creativity of the Karawo embroidery motifs at UMKM Serasi, Dulomo Selatan Village, Kota Utara Subdistrict, Gorontalo City. The effect of the training program on the creativity of the Karawo embroider motifs was 20,0%, while the remaining 80,0% were affected by other variables that were not exammed in this research.